1988
DOI: 10.1161/01.hyp.11.3.209
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of inhibition of human renin by monoclonal antibodies.

Abstract: SUMMARY The mechanism by which monoclonal antibodies directed against human renin (R3-36-16 and R3-47-10) inhibit renin activity was investigated using various substrates. Both antibodies acted as potent inhibitors of human renin activity when human angiotensinogen was used as a substrate. However, their effects differed clearly in the presence of synthetic tetradecapeptide. When low concentrations of tetradecapeptide were used as substrate, renin activity was only partially inhibited by R3-47-10, whereas it w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…We followed all American Heart Association Recommendations published in 1988 [8, 10] including using a 47 × 13 cm cuff and 24 × 13 cm bladder to avoid cuff hypertension. The cuff was strictly positioned 2 cm above the antecubital crease to obtain a similarly leveled complete compression of the brachial artery.…”
Section: Methodsmentioning
confidence: 99%
“…We followed all American Heart Association Recommendations published in 1988 [8, 10] including using a 47 × 13 cm cuff and 24 × 13 cm bladder to avoid cuff hypertension. The cuff was strictly positioned 2 cm above the antecubital crease to obtain a similarly leveled complete compression of the brachial artery.…”
Section: Methodsmentioning
confidence: 99%
“…These data suggest that Rl-20-5 is specific for the active site of renin. We have shown previously 20 that R3-36-16 induced an enhanced formation of Ang I from the reaction of renin with the synthetic substrate TDP. This effect was inhibited by CGP 29287.…”
Section: Resultsmentioning
confidence: 89%
“…Kinetic studies showed that Rl-20-5 is a competitive inhibitor similar to the peptidic transition state analogue CGP 29287 20 as analyzed using the MichaelisMenten equation or constraining the data with the ALLFIT program (Table 2, Figure 2). The maximum rate (VMJ) remained unchanged, whereas the Michaelis constant (K m ) increased threefold to fourfold, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Binding of an antibody to its cognate antigen can induce a conformational change in that antigen [5167]. Importantly, these conformational changes can lead to exposure of functional subdominant or neoepitopes [54, 60, 65, 6887], and such determinants can represent important targets of functional or neutralizing antibodies [62, 68, 88–97]. This is most evident in viral systems in which the availability of well-resolved crystal structures has outpaced that of bacterial molecules.…”
Section: Discussionmentioning
confidence: 99%